Open access to large scale datasets is needed to translate knowledge of cancer heterogeneity into better patient outcomes. - Andrew H Beck (PLoS Medicine)
In this guest editorial, Andrew Beck discusses the importance of open access to big data for translating knowledge of cancer heterogeneity into better outcomes for cancer patients.